Factors associated with absenteeism in elderly nursing workers - Arianne Gueiros Ferreira; Maysa Rayanne Cardozo Lopes; Anna Karla de Oliveira Tito Borba; Ana Paula de Oliveira Marques; Fábia Alexandra Pottes Alves; Bruna Cyreno de Carvalho Lima (Universidade Federal do Rio Grande do Sul, 2022)
ABSTRACT Objective: To analyze the factors associated with absenteeism in elderly nursing workers. Methods: Cross-sectional study with 233 elderly nursing workers carried out in six hospitals in Recife, Pernambuco, Brazil. The data were analyzed using univariate analysis and multivariate regression. Results: Of the 233 elderly nursing professionals interviewed, self-reported absenteeism was present in 34.3% (80) participants. 20.1% (47) of them reported having missed a few days and 14.2% (33) having done so in many days. After adjusted analysis, only work hours and satisfaction with health influenced absenteeism. Conclusion: Absenteeism is a complex phenomenon which, among elderly nursing professionals, had a low prevalence and was associated with a workload of more than 40 hours a week and dissatisfaction with health. Therefore, further research is needed in the field to provide quality of life and better working conditions for nursing professionals and regulate their workload.